Correlation of Gleason Scores with Diffusion-Weighted Imaging Findings of Prostate Cancer. (15th December 2011) - Nagarajan, Rajakumar; Margolis, Daniel; Raman, Steven; Sheng, Ke; King, Christopher; Reiter, Robert; Thomas, M. Albert
Abstract : The purpose of our study was to compare the apparent diffusion coefficient (ADC) derived from diffusion-weighted imaging (DWI) of prostate cancer (PCa) patients with three classes of pathological Gleason scores (GS). Patients whose GS met these criteria (GS 3 + 3, GS 3 + 4, and GS 4 + 3 ) were included in this study. The DWI was performed using b values of 0, 50, and 400 s/mm 2 in 44 patients using an endorectal coil on a 1.5T MRI scanner. The apparent diffusion coefficient (ADC) values were calculated from the DWI data of patients with three different Gleason scores. In patients with a high-grade Gleason score (4 + 3 ), the ADC values were lower in the peripheral gland tissue, pathologically determined as tumor compared to low grade (3 + 3 and 3 + 4 ). The mean and standard deviation of the ADC values for patients with GS 3 + 3, GS 3 + 4, and GS 4 + 3 were 1.135 ± 0.119, 0.976 ± 0.103 and 0.831 ± 0.087 mm 2 /sec. The ADC values were statistically significant (P < 0.05 ) between the three different scores with a trend of decreasing ADC values with increasing Gleason scores by one-way ANOVA method. This study shows that the DWI-derived ADC values may help differentiate aggressive from low-grade PCa.